Measurement of hydrophobic forces in thin liquid films of water between bubbles and xanthate-treated gold surfaces. (November 2016) - Pan, Lei; Yoon, Roe-Hoan
Graphical Abstract: Highlights: The forces calculated from Laplace pressure match with those measured directly. Hydrophobic force in wetting films increases with water contact angle. Frumkin-Derjaguin isotherm is used to obtain the free energy isotherm for flotation. Short-range hydrophobic force is responsible for the rupture of wetting films. Abstract: In flotation, bubble-particle attachment occurs when the wetting films of water formed in between are destabilized by collector coating. In most cases, DLVO forces are repulsive and hence stabilize wetting films; therefore, it is necessary to consider the role of attractive hydrophobic force as a destabilizer. In this regard, hydrophobic forces have been measured by monitoring dynamic profiles of an air bubble in nanoscale as it approaches a flat surface using the method described previously (Pan et al., 2011). The measurements conducted with gold substrates contacted in a 10 −5  M potassium ethyl xanthate (KEX) show that hydrophobic force increases with increasing contact time and water contact angle. After an excessively long contact time, hydrophobic force is found to decrease possibly due to multi-layer adsorption of xanthate. The forces measured from dynamic film profiles are in good agreement with those measured directly using a specially designed force apparatus. Analysis of the force data using the Frumkin-Derjaguin isotherm shows that bulk of the energy gained during bubble-particle interaction is due to the work done by the hydrophobic force at short range to overcome the repulsive van der Waals force. At long-range, hydrophobic force facilitates the kinetics of film thinning by reducing the force barrier created by double-layer force.